TACE antagonists blocking ACE2 shedding caused by the spike protein of SARS-CoV are candidate antiviral compounds - Haga, Shiori; Nagata, Noriyo; Okamura, Tadashi; Yamamoto, Norio; Sata, Tetsutaro; Yamamoto, Naoki; Sasazuki, Takehiko; Ishizaka, Yukihito (Antiviral research, 2010)
Because outbreaks of severe acute respiratory syndrome coronavirus (SARS-CoV) might reemerge, identifying antiviral compounds is of key importance. Previously, we showed that the cellular factor TNF-α converting enzyme (TACE), activated by the spike protein of SARS-CoV (SARS-S protein), was positively involved in viral entry, implying that TACE is a possible target for developing antiviral compounds. To demonstrate this possibility, we here tested the effects of TACE inhibitors on viral entry. In vitro and in vivo data revealed that the TACE inhibitor TAPI-2 attenuated entry of both pseudotyped virus expressing the SARS-S protein in a lentiviral vector backbone and infectious SARS-CoV. TAPI-2 blocked both the SARS-S protein-induced shedding of angiotensin-converting enzyme 2 (ACE2), a receptor of SARS-CoV, and TNF-α production in lung tissues. Since the downregulation of ACE2 by SARS-S protein was proposed as an etiological event in the severe clinical manifestations, our data suggest that TACE antagonists block SARS-CoV infection and also attenuate its severe clinical outcome.